Characteristics and Origin of Methane Adsorption Capacity of Marine, Transitional, and Lacustrine Shales in Sichuan Basin, China. (21st April 2021) - Tang, Xianglu; Wu, Wei; Zhong, Guanghai; Jiang, Zhenxue; He, Shijie; Liu, Xiaoxue; Zhu, Deyu; Xue, Zixin; Zhou, Yuru; Yang, Jiajing
Abstract : Adsorbed gas is an important component of shale gas. The methane adsorption capacity of shale determines the composition of shale gas. In this study, the methane adsorption capacity of marine, transitional, and lacustrine shales in the Sichuan Basin was analyzed through its isothermal adsorption, mineral composition, water content, etc. The results show that the methane adsorption capacity of marine (Qiongzhusi Formation and Longmaxi Formation), transitional (Longtan Formation), and lacustrine (Xujiahe Formation and Ziliujing Formation) shales is significantly different. The Longtan Formation has the strongest methane adsorption capacity. This is primarily related to its high organic matter and organic matter type III content. The methane adsorption capacity of the lacustrine shale was the weakest. This is primarily related to the low thermal evolution degree and the high content of water-bearing clay minerals. Smectite has the highest methane adsorption capacity of the clay minerals, due to its crystal structure. The water content has a significant effect on methane adsorption largely because water molecules occupy the adsorption site. Additionally, the temperature and pressure in a specific range significantly affect methane adsorption capacity.